Two new species of Cryptanthus (Bromelioideae, Bromeliaceae) from northeastern Brazil - Ferreira, Débora Maria Cavalcanti; Almeida, Erton Mendonça De; Louzada, Rafael Batista (Phytotaxa, 2021)
Two new species of Cryptanthus from Bahia State, in northeastern Brazil, are described and illustrated. Cryptanthus apiculatantherus occurs in Atlantic Forest and Cryptanthus brevibracteatus was discovered in a transition area between Atlantic Forest and Caatinga. Cryptanthus apiculatantherus and C. bibarrensis have similar stem lengths and leaf blade shapes, but differ mainly by the stem diameter, width of the leaf sheaths, sepal and petal color, anther apex shape, and length and width of the ovary. Cryptanthus brevibracteatus and C. warren-loosei have a similar leaf blade color and are geographically close to each other, but differ by the number of flowers in the apical cluster of flowers of the inflorescence, length and width of the floral bracts, length of the sepals, connation of the sepals and length of the sepal lobes. Data about the geographic distribution, habitat, phenology, conservation status, taxonomic comments, a distribution map and photographs of the new species are provided. In addition, there are tables included that compare the new species to morphologically similar species.